2013
DOI: 10.1037/a0031510
|View full text |Cite
|
Sign up to set email alerts
|

The comparative effect of subjective and objective after-action reviews on team performance on a complex task.

Abstract: The after-action review (AAR; also known as the after-event review or debriefing) is an approach to training based on a review of trainees' performance on recently completed tasks or performance events. Used by the military for decades, nonmilitary organizations' use of AARs has increased dramatically in recent years. Despite the prevalence of AARs, empirical research investigating their effectiveness has been limited. This study sought to investigate the comparative effectiveness of objective AARs (reviews ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 53 publications
1
92
0
1
Order By: Relevance
“…AARs have been found to increase leadership behavior following a leadership development program, especially for learners who have had challenging work experiences and are high in conscientiousness, openness to experience, and emotional stability (DeRue et al 2012b). Villado & Arthur (2013) found that student teams who used AARs, compared with those who did not, had enhanced team performance, team efficacy, openness of communication, and cohesion, but not team declarative knowledge. AARs were equally effective regardless of whether the feedback given was subjective or objective.…”
Section: Prelearning Interventions and Transfer Of Trainingmentioning
confidence: 99%
“…AARs have been found to increase leadership behavior following a leadership development program, especially for learners who have had challenging work experiences and are high in conscientiousness, openness to experience, and emotional stability (DeRue et al 2012b). Villado & Arthur (2013) found that student teams who used AARs, compared with those who did not, had enhanced team performance, team efficacy, openness of communication, and cohesion, but not team declarative knowledge. AARs were equally effective regardless of whether the feedback given was subjective or objective.…”
Section: Prelearning Interventions and Transfer Of Trainingmentioning
confidence: 99%
“…In addition to these three training approaches that occur outside of the team task environment (i.e., training within classroom and simulation settings), teamwork can also be fostered by incorporating team reviews in-situ (i.e., where the team actually performs its tasks), which allows teams to monitor/review their quality of teamwork on an ongoing basis. These team reviews involve some form of team briefs before (e.g., creating action plans), during (e.g., monitoring team members’ actions), and/or after (e.g., assessing the team’s performance) team task execution, and have also been shown to be efficacious in previous studies (e.g., [16]).…”
Section: Introductionmentioning
confidence: 99%
“…Learners can reflect on objective, video-based recordings or on subjective, memory-based recalls of their performance. Research has revealed that these ways of reflecting are equally effective (Villado & Arthur, 2013).…”
Section: When and For Whom Is Systematic Reflection Most Effective?mentioning
confidence: 99%